2018
DOI: 10.1186/s40104-018-0236-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary Bacillus amyloliquefaciens supplementation on growth performance, intestinal morphology, inflammatory response, and microbiota of intra-uterine growth retarded weanling piglets

Abstract: BackgroundThe focus of recent research has been directed toward the probiotic potential of Bacillus amyloliquefaciens (BA) on the gut health of animals. However, little is known about BA’s effects on piglets with intra-uterine growth retardation (IUGR). Therefore, this study investigated the effects of BA supplementation on the growth performance, intestinal morphology, inflammatory response, and microbiota of IUGR piglets.MethodsEighteen litters of newborn piglets were selected at birth, with one normal birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 83 publications
4
44
1
Order By: Relevance
“…Previous study demonstrated that the impaired intestinal morphology may be associated with the imbalance of cell apoptosis and proliferation [26]. In the current study, IUGR piglets enhanced the AI and reduced the PI of enterocytes when compared with NBW weaned piglets.…”
Section: Discussionsupporting
confidence: 58%
“…Previous study demonstrated that the impaired intestinal morphology may be associated with the imbalance of cell apoptosis and proliferation [26]. In the current study, IUGR piglets enhanced the AI and reduced the PI of enterocytes when compared with NBW weaned piglets.…”
Section: Discussionsupporting
confidence: 58%
“…The FSBM contained more probiotics and organic acids compared with SBM. It has been reported that probiotics and organic acids could regulate the production of cytokines and relieve ETEC K88-induced inflammation by suppressing the ETEC K88 proliferation and decreasing enterotoxin release [20][21][22][23]. This finding was also confirmed by the results of high-throughput sequencing, which shown that FSBM decreased the population of inflammation-related bacteria.…”
Section: Discussionmentioning
confidence: 56%
“…Thin sections (5 μm) from the jejunum were taken using a one-step terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) kit (#A113-03; Vazyme Biotech Co., Ltd., Nanjing, Jiangsu, China) to determine the apoptotic rate [32]. Each tissue section was permeabilized with a proteinase K solution (20 μg/mL) at room temperature for 20 min.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…In each slice, 15 random crypts were measured by an assessor blinded regarding the source of the samples. The cell proliferation index was calculated by dividing the number of Ki67-positive cells by the total number of crypt cells, based on the methods of previous studies [32,35].…”
Section: Immunohistochemistrymentioning
confidence: 99%